ANALISIS PELAKSANAAN SISTEM PELAYANAN OBSTETRI DAN NEONATAL EMERGENSI DASAR (PONED) DI PUSKESMAS SITANGGAL KABUPATEN BREBES - Valentina Ayumy Fortunita Mia; Anneke Suparwati; Antono Suryoputro (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
PONED is a health service to cope with cases of emergency obstetric and neonatal at the primary healthcare center level. Brebes that has the highest maternal mortality rate in recent years set 22 the primary healthcare center become PONED in 2015, one of which is Sitanggal. This purpose of this study is to describe and analyze the system implementation of PONED in the primary healthcare center Sitanggal from the aspects of input, process, output, feedback and environment. The type of observational study is a qualitative research with indepht interview. The study population were 4 key informants consisted of one team PONED (1 doctor and 2 nurses) with the heads of primary healthcare centers and 6 informants triangulation consisted of the kabid kesga DKK Brebes, 3 officers PONED (midwife) and 2 targets of PONED. The result shows that in the system implementation of PONED, from the aspect of input, there was no the assertiveness rules and an installed SOP as reference in PONED, there was a shortage of staff, there was only doctor in the morning shift, there was no specialized administrative staff, the condition of facilities and infrastructure were not supported the implementation of PONED yet. From the aspect of the process, there was no written document about organizing of PONED, some staffs did not obey the rules and another non-health staff still doubles as an staff in the primary healthcare center, the staff commitment was still difficult, there was no complete reporting document about the implementation of PONED in DKK. The aspect of output, the service by PONED in the primary healthcare center Sitanggal was low. From the aspect of feedback, there was no special evaluation that perfomed routinely by PONED. From the aspect of the environment, the support from the related parties was not maximed: The recommended suggestion are: to further reinforce the existing rules, the need for training and apprentice, procurement of equipment and better medicine, fostering the commitment to all related parties, reschedule the picket schedule, the need for coaching and routine evaluation in the implementation of PONED.